Mothers say “baby” and their newborns do not choose to listen: a behavioral preference study to compare with ERP results - Moon, Christine; Zernzach, Randall C.; Kuhl, Patricia K. (Frontiers in Human Neuroscience, 2015)
Previously published results from neonatal brain evoked response potential (ERP) experiments revealed different brain responses to the single word “baby” depending on whether it was recorded by the mother or an unfamiliar female. These results are consistent with behavioral preference studies in which infants altered pacifier sucking to contingently activate recordings of the maternal vs. an unfamiliar female voice, but the speech samples were much longer and information-rich than in the ERP studies. Both types of neonatal voice recognition studies imply postnatal retention of prenatal learning. The preference studies require infant motor and motivation systems to mount a response in addition to voice recognition. The current contingent sucking preference study was designed to test neonatal motivation to alter behavior when the reward is the single word “baby” recorded by the mother or an unfamiliar speaker. Results showed an absent or weak contingent sucking response to the brief maternal voice sample, and they demonstrate the complementary value of electrophysiological and behavioral studies for very early development. Neonates can apparently recognize the maternal voice in brief recorded sample (previous ERP results) but they are not sufficiently motivated by it to alter sucking behavior.